Characterization of solidifiers used for oil spill remediation. (February 2016) - Sundaravadivelu, Devi; Suidan, Makram T.; Venosa, Albert D.; Rosales, Pablo I.
Abstract: The physical characteristics and chemical composition of oil spill solidifiers were studied, and correlation of these properties with product effectiveness enabled determination of characteristics that are desirable in a good solidifier. The analyses revealed that the commercial products were primarily comprised of organic polymers and a few trace elements. A natural sorbent, which was composed entirely of plant based matter, was also evaluated, and it had the highest oil removal capacity, but it did not produce a solid mat-like final product. Generally, solidifiers with a carbonate group, pore size greater than 5 μm, and bulk densities lower than 0.3 g cm −3 were found to have better efficiency and produced a cohesive rubbery final product that facilitated removal compared to sorbents. The importance of bulk density and pore size in the performance of the solidifier suggest that the primary mechanism of action was likely physical sorption. Highlights: Oil solidifier products were characterized with FTIR, XPS, SEM, EDX. Most products were low density polymers or copolymers with trace amounts of Ca and Si. Products with decreasing carbon content, increasing Ca content, and decreasing bulk density performed best. Inter-particle void volume and intra-particle pore size contribute towards product oil-removal efficiency. Cohesiveness, consistency, and ease of removal of the final product were better for the low density polymeric solidifiers.